2015
DOI: 10.1098/rsbl.2015.0517
|View full text |Cite
|
Sign up to set email alerts
|

Stressful colours: corticosterone concentrations in a free-living songbird vary with the spectral composition of experimental illumination

Abstract: Organisms have evolved under natural daily light/dark cycles for millions of years. These cycles have been disturbed as night-time darkness is increasingly replaced by artificial illumination. Investigating the physiological consequences of free-living organisms in artificially lit environments is crucial to determine whether nocturnal lighting disrupts circadian rhythms, changes behaviour, reduces fitness and ultimately affects population numbers. We make use of a unique, large-scale network of replicated fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 17 publications
(24 reference statements)
6
66
2
Order By: Relevance
“…artificial light) can imitate ancestral cues (natural light) and animals exposed to this new environment may change their behaviour with innate responses that are no longer adaptive (Blumstein & BergerTal, 2015). Early singing may for example lead to sleep deprivation (Raap, Pinxten, & Eens, 2015) or to increased stress levels (Ouyang et al, 2015). Further work should also investigate whether songbirds can lower these potential costs by using (adaptive) compensatory behaviours (Sih et al, 2011) such as light avoidance, increased foraging, or decreased song output later during the day.…”
Section: Resultsmentioning
confidence: 99%
“…artificial light) can imitate ancestral cues (natural light) and animals exposed to this new environment may change their behaviour with innate responses that are no longer adaptive (Blumstein & BergerTal, 2015). Early singing may for example lead to sleep deprivation (Raap, Pinxten, & Eens, 2015) or to increased stress levels (Ouyang et al, 2015). Further work should also investigate whether songbirds can lower these potential costs by using (adaptive) compensatory behaviours (Sih et al, 2011) such as light avoidance, increased foraging, or decreased song output later during the day.…”
Section: Resultsmentioning
confidence: 99%
“…While artificial light affects circadian and circannual biology, the consequences on an individual's health and fitness under actual conditions remain unknown. We found that great tits roosting in white light have higher stress hormone concentrations (Ouyang et al., ), but it is uncertain if the cause is due to changes in behavior or the result of a direct physiological effect. Glucocorticoids, like those found to be elevated in the great tits, can be immunosuppressive (Nelson, Demas, Klein, & Kriegsfeld, ).…”
Section: Introductionmentioning
confidence: 93%
“…ALAN can affect several behaviors of wild animals, from orientation and navigation during dispersal and migration (Rich and Longcore, 2006;Poot et al, 2008), to daily and seasonal rhythms in behavior Robert et al, 2015;Dominoni et al, 2016), to more subtle physiological effects on stress levels, body mass and immune responses (Bedrosian et al, 2011;Ouyang et al, 2015;Raap et al, 2016a). Effects on circadian rhythms of behavior and physiology are particularly evident in a range of species, from insects to mammals (Swaddle et al, 2015).…”
Section: Introductionmentioning
confidence: 99%